Josef Andreas Jungmann SJ, Liturgia pierwotnego Kościoła do czasów Grzegorza Wielkiego, tłum. Teresa Lubowiecka, posłowie: ks. Helmut J. Sobeczko, Modlitwa Kościoła 16, Kraków 2013, Tyniec Wydawnictwo Benedyktynów, ss. 503. - Kalinowski, Damian (Vox Patrum, 2014)
nie dotyczy